Phytochemical Screening and Antimicrobial Activity of Ethanolic Extract of Lablab Purpureus - R. Shiva Prasad; D.Srilatha; Y.Srikanth; M.Nikita Singh; M.Meenakumari; J.V.C.Sharma (International Journal of Pharma and Bio Sciences, 2022)
The aim of the current study was to perform phytochemical screening and evaluating antimicrobial activity of Lablab Purpureus leaves extract by using disc diffusion method on different microorganisms. Gentamicin which is a commonly prescribed drug for Anti-microbial treatment was used as a reference drug for comparison. The Leaves of ethanolic extract of Lablab purpureus were subjected to the phytochemical screening and antimicrobial activity. Phytochemicals are the plant subsidiaries which are utilized mostly in natural medications. They cure many epidemic diseases. In the current study phytochemical analysis of Lablab purpureus L. showed the presence of phytoconstituents such as flavonoids, saponins, steroids, sugar, alkaloids, tannins, coumarins, terpenoids and other pigments. On the other hand, ethanolic extract showed a good antibacterial activity against Gram(-) bacteria, E.coli, P.aeruginosa, with a Zone of inhibition at a range 16 mm and 10 mm respectively at the selected concentrations, while ethanolic extract was reported to show zone of inhibition against staphylococcus epidermidis as 13 mm and Bacillus subtilis as 18 mm at the maximum concentration. P. aeruginosa showed no zone of inhibition to ethanolic leaf extract and S.epidermidis didn't respond to ethanolic extracts of lablab purpureus. Leaves extract of Lablab purpureus revealed moderate antimicrobial activity against some microorganisms used in the antimicrobial screening.